A Monoclonal Antibody Raised against Human β-factor XIIa which also Recognizes α-factor XIIa but not Factor XII or Complexes of Factor XIIa with C1 Esterase Inhibitor - Esnouf, M. Peter; Burgess, Annette I.; Dodds, Alister W.; Sarphie, Anna F.; Miller, George J. (Thrombosis and Haemostasis, 2000)
A monoclonal antibody (mAb 2/215) against human β-factor XIIa (β-FXIIa), was shown by equilibrium binding studies to have a high affinity for α-factor XIIa (α-FXIIa) (Kd 1.8 nM) and β-FXIIa (Kd 0.65 nM) but no detectable reaction with FXII zymogen or α - esterase inhibitor (C1-INH) complex. Surface plasmon resonance studies showed that the mAb 2/215 bound to immobilized α-FXIIa with high affinity (KD 3.93 ± 1.46 × 10−11 M). Western blots employing mAb 2/215 indicated that human plasma contained small amounts of α-FXIIa but no β-FXIIa. mAb 2/215 did not inhibit the amidolytic activity of β-FXIIa and protected β-FXIIa from inhibition by C1-INH. The recovery by ELISA ,employing mAb 2/215 as the capture antibody, of α-FXIIa added to plasma was 11.3%, 42% after inhibition of α-FXIIa with 3:4dichloroisocoumarin, and 82% when 0.5% TritonX100 was added to the assay. Gel filtration showed that the majority of plasma α-FXIIa existed as a complex (Mr ∼170000). This distinctive mAb increases the capacity to study the contact system in health and disease.
Keywords: Monoclonal antibody; factor XIIa; ELISA; affinity binding studies